Limitations in the use of fluorinated greenhouse gases in the production of polyurethane foams and systems - Kozakiewicz, J. (Polimery, 2021)
The paper contains a review of limitations in the use of fluorinated greenhouse gases (F-gases) in production of polyurethane foams and systems (PUR) at a global level (Kigali Amendment to the Montreal Protocol), European level [Regulation (EU) No. 517/2014] and national level (revised Act on substances that deplete the ozone layer and on certain fluorinated greenhouse gases). The obligations of entities conducting activities in PUR foam and systems sector that relate to F-gases and result from European Union and Polish legislations are described. The list of F-gases and their alternatives which are currently used in PUR foams and systems is revealed and the forecast of the increase of global demand for those substances as well as percentage of share of individual F-gases in total quantity of F-gases applied in production of PUR foams and systems in Poland is presented.